Evidence-based practice in school mental health a primer for school social workers, psychologists, and counselors - Raines, James Curtis (Oxford : Oxford University Press, 2008)
This title guides school professionals in infusing research throughout their daily practice. It shows school service providers a pragmatic approach to informing every major practice decision with the appropriate research so that students receive the best possible services.
Description based on print version record.
Includes bibliographical references and index.
Keywords: School children -- Mental health services; School social work -- United States; Evidence-based social work -- United States; Evidence-based psychiatry -- United States; Students with disabilities -- Services for -- United States